Testing The Effectiveness Of Biological Herbicide In Coffee Plantations In Various Agro-ecological Conditions - Anwar, Risvan; Suzanna, Eka; Djatmiko, Djatmiko (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
This study aims to determine the effectiveness of biological herbicide formulas on smallholder coffee plantations in various agro-ecological conditions, namely smallholder coffee fields in the medium plains and plateau. The study concluded that the weeds found in the medium plains coffee fields were 17 species. The dominant weeds were Cynodon dactilon 38.1%, Asystasia gangetica 19.3%, Ageratum conyzoides 10%, Borreria latifolia 5.4%, Acmella paniculata 3.3%, and Clydemia hirta 3.3%. These six types of weeds dominate the land at 79.4%. Meanwhile, in the plateau, there were 20 types of weeds. The dominant weeds were Brachiaria ramosa 17.8%, Synedrella nodiflora 10.4%, Digitaria cyliaris 8.7%, Mikania micrantha, 8.7%, Brachiaria setigera 8.5%, Dryopteris filixmas 7.8%, Ottochloa nodosa. 5.7%, Hyptis rhomboidea 4.3%, Brachiaria reptans 3.9%, and Clidemia hirta 3.5%. These ten types of weeds dominate the land for 79.3%. Herbicides formulated Unihaz 3, 4, 5, 6, and 7 were effective in controlling weeds in smallholder coffee plantations, both in the medium plains and plateau.